KARAWITAN TARI GOLEK AYUN-AYUN KARYA K.R.T.SASMINTADIPURA: KAJIAN POLA GARAP KENDHANGAN - Feri Darmawan (Saraswati)
Golek Ayun-ayun is a classical dance Yogyakarta style created by K.R.T. Sasmintadipura. She is a classical dancer Yogyakarta style that is also the founder of the Foundation Pamulangan Beksa Sasminta Mardawa. Golek Ayun-ayun dance has several features of which are located in the drum pattern. If the uyon-uyon wearing a drum pattern that is certain however, Ayun-ayun puppet dance has a very different drum pattern. In this way, expected to be revealed some differences in the pattern ofworking on a drum in the presentation of dance Golek Ayun-ayun is, and because it uses gising Ladrang Ayun-ayun then the dances called by Golek Ayun-ayun. While the dance depicts a young woman who was preening or makeup to make herself then, in the dance movements are ngenggar sinom which means straighten hair on the forehead, which means miwir rikma straighten hair.Keyword: Tari, karawitan, golek